A socioecological examination of father alcohol use in Kenya: Motivation, consequences, and barriers to care - Ali Giusto; Emily N. Satinsky; Florence Jaguga; Wilter Rono; Julius Barasa; Chardée A. Galán; Milton L. Wainberg (Global Public Health)
Fathers’ alcohol use impacts family well-being, including increased risk for violence, poor child outcomes, and low engagement in care. Yet few studies examine the drivers of alcohol use among fathers or the role of gendered expectations and sociocultural norms on use, especially in low-resource settings like Kenya. Understanding why fathers drink, the consequences of use, and barriers to care is key to designing scalable, responsive interventions. In Eldoret, Kenya, community members, leaders, providers, and fathers experiencing problematic alcohol use participated in interviews and focus groups. Participants discussed reasons for drinking, its impacts, and barriers to care. Using the framework method, transcripts were coded and summarised using the socioecological model. Reasons and consequences of alcohol use emerged across individual, interpersonal, and sociocultural levels. Individually, fathers used alcohol to escape distress with consequences on physical and mental health. At the family level, alcohol was used to avoid conflict, contributing to risk for violence and poor child outcomes. Socioculturally, drinking was shaped by gender norms, with consequences like stigma and loss of social status, which reinforced shame and isolation. Barriers to care included lack of awareness, poor service access, and stigma. Intervention and implementation strategies must address avoidant coping, masculinity norms, and local resource constraints.